Developing imprinted polymer nanoparticles for the selective separation of antidiabetic drugs. Issue 19 (1st September 2015) - Haq, Isma; Mujahid, Adnan; Afzal, Adeel; Iqbal, Naseer; Bajwa, Sadia Zafar; Hussain, Tajamal; Shehzad, Khurram; Ashraf, Hadia
<x xml:space="preserve">Abstract</x> In this study, new molecularly imprinted polymer (MIP) nanoparticles are designed for selective recognition of different drugs used for the treatment of type 2 diabetes mellitus, i.e. sitagliptin (SG) and metformin (MF). The SG‐ and MF‐imprinted polymer nanoparticles are synthesized by free‐radical initiated polymerization of the functional monomers: methacrylic acid and methyl methacrylate; and the crosslinker: ethylene glycol dimethacrylate. The surface morphology of resultant MIP nanoparticles is studied by atomic force microscopy. Fourier transform infrared spectra of MIP nanoparticles suggest the presence of reversible, non‐covalent interactions between the template and the polymer. The effect of pH on the rebinding of antidiabetic drugs with SG‐ and MF‐imprinted polymers is investigated to determine the optimal experimental conditions. The molecular recognition characteristics of SG‐ and MF‐imprinted polymers for the respective drug targets are determined at low concentrations of SG (50–150 ppm) and MF (5–100 ppm). In both cases, the MIP nanoparticles exhibit higher binding response compared to non‐imprinted polymers. Furthermore, the MIPs demonstrate high selectivity with four fold higher responses toward imprinted drugs targets, respectively. Recycled MIP nanoparticles retain 90% of their drug‐binding efficiency, which makes them suitable for successive analyses with significantly preserved recognition features.